Spore 190: Farm data - Serving smallholder farmers in a digital age - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
Increasing amounts of agricultural data are being produced at faster speeds, using a greater variety of technologies and innovations than ever before. But what is the value of information sharing for smallholders, and what are the risks?